Menghitung Peluang dalam Susunan Kata Sandi : Kombinatorika dalam Keamanan Digital - Arnah Ritonga; Dina Harianja; Maisarah Putri Lalyta Siregar; Stepanus Simatupang; Vany Aisah Panggabean (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Today is a sophisticated era where everything is digital, be it smartphones, laptops, even safes. So digital password security is essential in protecting personal data. This study analyzes password strength using combinatorics and probability. Calculations are made to determine the number of possible password combinations based on the length and type of characters. In addition, the probability of success of a brute-force attack is calculated based on the number of guesses that can be made by the attacker. The results show that the longer and more complex the password, the less likely it is to be guessed. This study also discusses the concept of information entropy to measure the level of randomness of passwords and its impact on digital security. This study provides insight into the importance of choosing strong passwords.